Endoscopic papillary large balloon dilation and endoscopic papillary balloon dilation both without sphincterotomy for removal of large bile duct stones: A propensity‐matched analysis. Issue 1 (26th July 2018) - Hakuta, Ryunosuke; Kawahata, Shuhei; Kogure, Hirofumi; Nakai, Yousuke; Saito, Kei; Saito, Tomotaka; Hamada, Tsuyoshi; Takahara, Naminatsu; Uchino, Rie; Mizuno, Suguru; Tsujino, Takeshi; Tada, Minoru; et al.
Abstract : Background and Aim: Endoscopic papillary large balloon dilation (EPLBD) without endoscopic sphincterotomy (EST) may facilitate extraction of large bile duct stones through achieving adequate dilation of the ampulla. However, contrary to favorable long‐term outcomes after endoscopic papillary balloon dilation (EPBD), that of EPLBD without EST has been little investigated. Therefore, we conducted the current study to evaluate short‐ and long‐term outcomes of EPLBD without EST and EPBD after removal of large bile duct stones (LBDS; ≥10 mm). Methods: This retrospective study included patients without a previous history of EST, EPBD or EPLBD who underwent EPLBD without EST or EPBD for removal of LBDS. Each patient in the EPLBD without EST group was matched to a patient in the EPBD group using propensity scores. Results: Forty‐four patients in each group were matched for the analysis. Baseline characteristics were balanced after propensity matching. Rate of complete stone removal in a single session was higher (80% vs 16%, P < 0.001), number of ERCP sessions (1.3 ± 0.7 vs 2.4 ± 1.5, P < 0.001) and rate of lithotripsy use (30% vs 80%, P < 0.001) were smaller in the matched EPLBD without EST group. Contrary to null between‐group differences in early adverse events ( P = 0.99), a cumulative rate of late biliary complications was higher in the EPLBD without EST group ( P = 0.02). Conclusion: EPLBD without EST showed higher efficacy for removal of LBDS but was associated with worse long‐term outcomes when compared to EPBD.